(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
One of the most widely used Ayurvedic dosage forms is Sneha Kalpana. An Oleaginous Medication is prepared through a pharmaceutical process, includes heating of materials (Drava Dravyas, Kwatha, Kalka) in a prescribed pattern for a preordain duration. This process ensures the extraction of chemical constituents into an oil or fat base. Acharya Sushruta mentioned Ropana Taila in Sutrasthana Ch36/25, which has wound healing activity. It contains Haridra, Agaru, Daruharidra, Devdaru, Priyangu, Agaru, Lodhra, Tagara, and Tila Taila. Aim: The aim of the study was to standardize the pharmaceutical process, perform possible analytical parameters and its modification into ointment with suitable excipients. Methods: The general method of preparation of Taila Paka according to the classical text has followed for the preparation of Ropana Taila. An attempt has made to develop suitable dosage foam, an ointment from Ropana Taila. The preliminary analysis of raw materials and Ropana Taila has carried out with reference to the API standards. Possible evaluation parameters of the ointment have studied. Result: Physico-chemical parameters for Ropana Taila included specific gravity, which founded 0.9128, refractive index 1.471, viscosity 37.85, iodine value 110; acid value 4.1, and saponification value 182.33 has noted. HPTLC showed variable numbers of spots when visualized at 254nm, 366nm, and 510nm wavelengths. pH, spreadability, extrudability of ointment founded 6.5, 78mm, good respectively. Conclusion: The ratio adopted for the preparation of Ropana Taila ointment has found suitable as the ointment fulfilled the evaluation parameters for the quality of the ideal ointment.